Effect of Foreign Portfolio Investment in Bond Stocks on the Performance of the Nigerian Stock Market - Iriobe, Grace O.; Obamuyi, Tomola Marshal; Abayomi, Muftau A. (Archives of Business Research, 2018)
Emerging markets like Nigeria have consistently utilized foreign portfolio investments inflows to boost the economy. While economies consistently harness Foreign Portfolio Investment (FPI) in equity stocks to grow the economy, the report on foreign portfolio investments in bond stocks is too low to bridge the savings-investment gap in the economy. Therefore, this study examines the effect of foreign portfolio investment in bond stocks on the performance of the Nigerian stock market. The study employed ex-post facto research method using monthly time series data from 2007 to 2017. Using the Auto-Regressive Distributed Lag (ARDL) model, the study found that foreign portfolio investment in bond stocks have a positive and significant influence on the Nigerian stock market performance at 5% level (t-stat= 2.91380, P= 0.0038<0.05; R2 = 0.73). The study concludes that foreign portfolio investment in bond stocks significantly predict stock market performance in Nigeria, and therefore recommends that the market regulators need to further encourage foreign investments in bond stocks as this financial instruments do not attract much investment as equity stocks. Also, there is need for sound corporate governance and transparency as well as full disclosure of financial information by listed firms in order to increase the attraction of foreign portfolio investment in debt stocks[U1] to Nigeria. [U1]as amended